REVISION OF SOME CAMBRIAN BRADORIIDS (CRUSTACEA) FROM THE SIBERIAN PLATFORM - Melnikova L.M. (My University, 1998)
The species Bradoria ordinata Melnikova, 1983 is revised on the basis of additional material from the Cambrian of the middle reaches of the Lena River. The systematic position of the bradoriid species previously assigned to the genus Sunella Huo, 1965 is revised. Two new genera are established: Sinskolutella gen. nov. including B. ordinata (type species) and Leperditia? concentrisulcata Abushik, 1960 and Yakutingella gen. nov. including Y. intricata sp. nov. (type species) and Sunella parva Melnikova, 1988. The genus Duibianella Shu, 1990 previously known only from the Lower Cambrian of China was also discovered in the studied sequence.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская